The Efficacy and Safety of Thrice vs Twice per Week Low-Intensity Pulsed Ultrasound Therapy for Erectile Dysfunction: A Randomized Clinical Trial. Issue 10 (20th August 2022) - Chen, Huirong; Li, Zheng; Li, Xianchen; Yang, Yong; Dai, Yutian; Xie, Zuogang; Xiao, Jiaquan; Liu, Xiaoqiang; Yang, Luo; Shi, Chenkun; Zhi, Erlei; Tian, Ruhui; et al.
ABSTRACT: Background: A recent sham-controlled clinical study has shown that low-intensity pulsed ultrasound twice per week can safely and effectively treat patients with mild-to-moderate erectile dysfunction (ED). However, large-scale clinical trials are needed to verify its efficacy and safety and determine a reasonable treatment interval. Aim: To study whether low-intensity pulsed ultrasound therapy thrice per week is non-inferior to twice per week in patients with mild-to-moderate ED. Methods: A randomized, open-label, parallel-group, non-inferiority clinical trial was conducted in 7 hospitals in China. A total of 323 patients with mild-to-moderate ED were randomized (1:1) into thrice per week (3/W) and twice per week (2/W) groups. Low-intensity pulsed ultrasound was applied on each side of the penis for 16 sessions. Outcomes: The primary outcome was response rate using the minimal clinically important difference in the International Index of Erectile Function (IIEF-EF) score at week 12. Secondary outcomes included Erection Hardness Score (EHS), Sexual Encounter Profile, Global Assessment Question, and Self Esteem and Relationship Questionnaire. Results: Response rates in 3/W and 2/W groups were 62.0% and 62.5%, respectively. Treatment effect in the 3/W group was noninferior to that of the 2/W group, with rate difference lower bound of −0.01% [95% confidence interval −0.11 to 0.10%] within the acceptable margin (−14.0%). No significant difference was found among secondary outcomes. IIEF-EF score showed a significant increase from baseline in the 3/W group (16.8 to 20.7) and 2/W group (17.8 to 21.7), and the percentage of patients with EHS ≥3 increased in the 3/W (54.9% to 84.0%) and 2/W (59.5% to 83.5%) groups. There was no significant difference in response rate between the 2 groups after controlling for strata factors and homogeneous tests. No treatment-related adverse events were reported. Clinical Implications: Low-intensity pulsed ultrasound therapy displays similar efficacy and safety for mild-to-moderate ED when administered thrice or twice per week for 16 sessions. This study provides two options to suit patients' needs. Strengths & Limitations: This is a large-sample, randomized, controlled, noninferiority trial study. Short-term follow-up and mostly younger patients are the main limitations. Conclusion: Low-intensity pulsed ultrasound therapy thrice and twice per week showed equivalent therapeutic effects and safety for mild-to-moderate ED in a young and generally healthy population. This therapy warrants further investigation of its potential value in rehabilitation of ED.